Factors Influencing The Revenue Of Broiler Open House System Partnership Corporate X In Indonesia: Factors Influencing The Revenue Of Broiler Open House System Partnership, Corporate X In Indonesia - Niswatin Hasanah; Zaenal Fanani (Journal of Development Research, 2018)
The objective of research is to understand factors influencing the revenue of broiler farming. Re-search starts from June to July 2015. Method of research is case study. Data collection technique in-cludes observation and interview. The interview is conducted with 30 broiler farmers selected through total sampling and also corporation X In Kediri Indonesia. Data analysis tool involves descriptive analysis, economic analysis and regression analysis with SPSS16. Result of research indicates that various strata can be arranged based on chicken ownership (breeding capacity), respectively 3,000-12,000 chickens for Strata I, 12,000-27,000 chickens for Strata II, and > 30,000 chickens for Strata III. Production cost, revenue and profit in Strata III are greater than those in Strata I and II. Factors influencing the revenue of breeder on period 1 -6 include feed cost, broiler sale and bonus. Based on financial analysis against broiler breeding, the breeding is profitable and also reliable pursuant to what has been shown by financial result.